(untitled) (Slavic Studies, 2025)
The focus of the analysis of this paper is on the orthographic-phonological peculiarities that are represented in two Church Slavonic manuscripts with a Macedonian Church Slavonic redaction. More precisely, on a comparison of the eras and the nasals in Radomir’s psalter and the Sloestich paterikon is carried out. Finally, the paper includes a tabular presentation containing a detailed analysis of the differences and similarities that the subject manuscripts have on the orthographic and phonological level.